2020
DOI: 10.1111/jocd.13843
|View full text |Cite
|
Sign up to set email alerts
|

Para rubber seed oil: The safe and efficient bio‐material for hair loss treatment

Abstract: Para rubber is the important agricultural crops of the world. 1,2 This natural rubber has been serving for biomedical applications in several form of devices and products. Of which, the most obvious well-known form is latex globe. 3 Novel uses of para rubber seed is sparely to be presented in spite of a huge abandoned portion that dramatically increases with the tree planting for latex production.The seed was reported to be used for animal feeds, bio-fuels, and painting industry. [4][5][6] Nonetheless, alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…These cells have been used as an in vitro model to examine how herbal extracts or other compounds influence the expression of the SRD5A gene in order to screen for antagonism to androgens for the prevention of hair loss. [20,21]. Likewise, HFDPC, which are specialized mesenchymal cells found at the base of hair follicles and are important in hair follicle formation and postnatal hair growth cycles, are used as an in vitro model to assess the cellular and molecular effects of hair growth-moderating substances as well as their effects on 5α-reductase activity [22].…”
Section: Introductionmentioning
confidence: 99%
“…These cells have been used as an in vitro model to examine how herbal extracts or other compounds influence the expression of the SRD5A gene in order to screen for antagonism to androgens for the prevention of hair loss. [20,21]. Likewise, HFDPC, which are specialized mesenchymal cells found at the base of hair follicles and are important in hair follicle formation and postnatal hair growth cycles, are used as an in vitro model to assess the cellular and molecular effects of hair growth-moderating substances as well as their effects on 5α-reductase activity [22].…”
Section: Introductionmentioning
confidence: 99%
“…The modulation of the SRD5A gene expression was observed in prostate tumor cells as previously described [ 10 ]. The DU-145 cells were used as an in vitro cell model to determine the expression of 5α-reductase for anti-hair loss applications [ 100 , 101 , 102 ] because the action of 5α-reductase was obviously evaluated in prostate cells [ 103 ]. Total RNA was isolated from the DU-145 cells treated with samples (RBO, 0.25 mg/mL; DFRB, 0.50 mg/mL; and H, 0.10 mg/mL) or SRD5A enzyme inhibitors (dutasteride and finasteride at a concentration of 0.10 mg/mL) for 24 h. The RNA extraction process was performed using the E.Z.N.A.…”
Section: Methodsmentioning
confidence: 99%
“…Downregulation of SRD5A gene expression could lead to a reduction in their protein translation in the downstream pathways involving the pathology of AGA. Several studies have indicated that the DU-145 human androgen-insensitive prostate adenocarcinoma cell line expresses the three types of SRD5A; these cells have been used in the present study to observe the regulation of SRD5A gene expression [16,28,74,75]. With regards to these, the effects of the selected bioactive compounds and rice bran extracts on SRD5A1, SRD5A2, and SRD5A3 expression were investigated.…”
Section: Effect On the Expression Of 5-alpha Reductase Isoenzymesmentioning
confidence: 99%